BUSINESS ANALYSIS OF CULTIVATION OF PATIENT FISH (PangasiusSutchi) IN THE POOL IN RIVER VILLAGE LIPAI SUB DISTRICT GUNUNG SAHILAN KAMPAR DISTRICT RIAU PROVINSCE - Rio Deby; Hendrik Hendrik; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Research on the Analysis of Patent Fish Enlargement Business (PangasiusSutchi) In pond was conducted in May 2018 in GunungSahilan Sub-District, Kampar District, Riau Province. This study aims to (1) find out the amount of investment costs in the business of fish enlargement Patin in ponds, (2) to analyze the feasibility of Patin fish enlargement in the pond. The method used is survey method which includes observation, interview and documentation.  Based on the result of the research (1) the input in Patin fish enlargement effort is density of stocking in each pond with the width of 300-850 m2 as much as 4500-12750 tail / pond and the output in Patin fish enlargement business is the amount of production in each pond as much as 1507 -4271 Kg / pool. average production cost incurred at Patin fish raising business with 300-850 m2 pool area IDR 23.628.850, - / harvest up to IDR 67.123.050, - / harvest with total receipt received IDR 27.126.000, - / harvest to IDR 76.878.000, - / harvest and profit received IDR 3.497.150, -panen to IDR 9.754.950, - / harvest and (2) Patin fish breeding business in pond in Sungai Lipai worthy of RCR > 1, with FRR value> 6,02% and PPC value that is between 7,56-8,36 per period or ± 7 year 8 months. Keywords: Patin Fish Enlargement, Business Analysis, Lipai River